Comparative "virtual biopsies" of normal skin and skin lesions using vibrational optical coherence tomography. Issue 5 (24th May 2019) - Silver, Frederick H.; Shah, Ruchit G.; Richard, Michael; Benedetto, Dominick
Abstract: Background: Increased tissue stiffness (also termed modulus) has been shown to be a characteristic of potential tumor metastasis. Measured values of the stiffness of tumors and cancer cells are reported in the literature to increase compared to neighboring normal tissues. Yet the relationship between the mechanical properties of cells and the extracellular matrix has yet to be correlated with the histopathology of cancerous lesions. Materials and Methods: We have developed a technique to do virtual biopsies of skin lesions by combining images made using optical coherence tomography with stiffness measurements made simultaneously using vibrational analysis. The technique is termed vibrational optical coherence tomography (VOCT). Results: In this paper, we report that precancerous and cancerous lesions are characterized by changes in both the morphology and stiffness of the cellular components of the skin. The ratio of the peak heights that correspond to the epidermal (40‐60Hz) and dermal (140‐160 Hz) resonant frequencies appear to be different for benign and cancerous or precancerous lesions compared with normal skin and scar. Conclusions: Cell‐to‐cell and epidermal‐to‐dermal interactions may be very important in evaluating the potential of skin lesions to become malignant. These interactions can be evaluated using VOCT, a new technique for performing "virtual biopsies" of skin lesions.